Politeness Maxims in Dialogue Toy Story 4 Movie - Artha, Bagus Teresna Binaning; Udayana, I Nyoman; Sedeng, I Nyoman (Stilistika : Journal of Indonesian Language and Literature, 2022)
This study is entitled Politeness Maxims in Dialogue Toy Story 4 Movie. This study aimed to observe the types of politeness maxims and the functions of politeness maxims applied in the movie. The Toy Story 4 Movie uses a data source in this study because there had been conversations related to politeness expressions with all characters. This study uses the documentation method and note-taking technique in collecting the data. The data of this study were analyzed using the descriptive qualitative method and using the theory of pragmatics by Leech (1983). However, this study only focuses on four maxims as Generosity maxim, Approbation maxim, Agreement maxim, and Sympathy maxim to facilitate research. Based on the analysis, the results show that all four maxims can be found in this study. The most dominant maxim which was used in this study is Generosity maxim and Agreement maxim while the most functions applied in each politeness maxims is Irony.